2023
DOI: 10.1021/acs.inorgchem.3c00421
|View full text |Cite
|
Sign up to set email alerts
|

Strong Magnetocaloric Coupling in Oxyorthosilicate with Dense Gd3+ Spins

Abstract: Searching for working refrigerant materials is the key element in the design of magnetic cooling devices. Herein, we report on the thermodynamic and magnetocaloric parameters of an X 1 phase oxyorthosilicate, Gd2SiO5, by field-dependent static magnetization and specific heat measurements. An overall correlation strength of |J|S 2 ≈ 3.4 K is derived via the mean-field estimate, with antiferromagnetic correlations between the ferromagnetically coupled Gd–Gd layers. The magnetic entropy change −ΔS m is quite impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…The RCP data has been successfully adjusted to the power-law RCP ≈ ⟨ d Gd ⟩ q (i.e, ⟨ d Gd ⟩ is the Gd-relative density per molecular weight), yielding q = 0.92 ± 0.03, and demonstrating an almost linear relationship with the Gd-density. This RCP max value is higher than the one recently observed for Gd 2 SiO 5 (649.5 J/kg) . The divergence between Δ S M max and RCP is due to the larger δ T fwhm for Gd-UiO-66 compared to Gd-LRH, which induces an enhancement of the RCP value.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The RCP data has been successfully adjusted to the power-law RCP ≈ ⟨ d Gd ⟩ q (i.e, ⟨ d Gd ⟩ is the Gd-relative density per molecular weight), yielding q = 0.92 ± 0.03, and demonstrating an almost linear relationship with the Gd-density. This RCP max value is higher than the one recently observed for Gd 2 SiO 5 (649.5 J/kg) . The divergence between Δ S M max and RCP is due to the larger δ T fwhm for Gd-UiO-66 compared to Gd-LRH, which induces an enhancement of the RCP value.…”
Section: Resultsmentioning
confidence: 52%
“…However, this is not the case for the total angular momentum ( J ), as it does not display any trend depending on the rare-earth ion (see Figure ). Specifically, the highest −Δ S M max , which corresponds to Gd-RPF-4, is due to the particularity of the large spin ground state with zero orbital moment ( S = 7/2 and L = 0, i.e., J = 7/2), where Gd 3+ has a spherically symmetric ground state of 8 S 7/2 which provides the largest entropy per single ion, and an overall crystal field splitting of 1 K magnitude. , Moreover, its weak superexchange interactions result in low-lying excited spin states . On the other hand, even if the Ho ion has a greater J = 8 ( S = 2 and L = 6), the corresponding MOF only yields a −Δ S M max of 3.71 J/kg·K at 17 K. Thus, from the magnetization point of view, we observed that PM moment and M S play an important role in enhancing the magnetic entropy change values in the α-RPF-4 series.…”
Section: Resultsmentioning
confidence: 99%
“…We then adopt a nearest‐neighbour Heisenberg model to characterize the bulk magnetic behaviour, by writing the spin Hamiltonian scriptHbadbreak=J1badbreak<i,jgoodbreak>Si·Sjgoodbreak+Hdip$$\begin{equation} \mathcal{H}={J}_{1}\sum _{&lt;i,j&gt;}{S}_{i}\cdot {S}_{j}+{H}_{\mathrm{dip}} \end{equation}$$of which J 1 represents the Heisenberg exchange interactions between the nearest neighbour spin pairs, and H dip denotes the magnetic dipolar interactions. [ 7,16,19 ] Although the magnetic anisotropy is considered important in some Gd 3+ clusters, we exclude the single‐ion anisotropy term for the eightfold degenerate spin multiplet of Gd 3+ ( L = 0, S = J = 7/2) here, following a similar approach employed in studies on garnet GGG and tripod kagome magnet Mg 2 Gd 3 Sb 3 O 14 . [ 20 ] The relevant dipolar energy scale is D dip = 0.65 K, using the crystallographic Gd 3+ …Gd 3+ separation in triangle Gd 1.00 −(6 h ) chain, accounts for no more than 29% of the antiferromagnetic couplings.…”
Section: Resultsmentioning
confidence: 99%
“…[2b-d,3] The spinonly Gd 3+ compounds, with large J = S = 7/2 and g J = 2, then become rather appealing, as in the case of the benchmark refrigerant Gd 3 Ga 5 O 12 (GGG), and the alternative dipolar antiferromagnet LiGdF 4 . [2f,3b,4] Many other potential working materials, including the GdPO 4 , [5] NaGdS 2 , [6] Gd 2 SiO 5 , [7] Sr 2 GdSbO 6 , [8] Gd(HCOO) 3 , [9] Gd(OH)CO 3 , [10] GdF 3 [11] and Gd(OH)F 2 , [12] as well as the molecular {Gd 12 Na 6 } quadruplewheel are identified. [13] In most cases, the volume of refrigerant dominates the magnet system and the associated shielding, which must be minimized during space missions, thereby posing a challenge in identifying magnetocaloric materials with a large volumetric cooling capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation